(untitled) (Research, Society and Development, 2021)
Introduction: Sexually transmitted infections (STIs) are a matter to be discussed in public health, they are among the main causes of seeking care in the world, they affect both sexes, being explicit in maternal and child mortality. Objective: To clarify the main most common STIs during the pregnancy period, and which are the most recurrent maternal-infant complications. Methodology: This is a systematic review of the literature of a qualitative nature, related to complications due to STIs during pregnancy. To identify studies, searches were performed in electronic databases, Latin American (LILACS), US National Library of Medicine (PUBMED), Cumulative Index to Nursing & Allied Health Literature (CINAHL), SciVerse Scopus (SCOPUS), Cochrane Library (COCHRANE) and Google Scholar. With the following search strategy through the crossing of descriptors using the logic of Boolean resources in the search field, in the period from 2016 to 2021. Result: Pregnant women who do not use condoms are at the highest risk of contracting an STI and preconception and prenatal screening in the mother, or neonatal screening in the child, which are available, is essential for early diagnosis and treatment. Conclusion: The nurse in these situations is a main agent in primary care through prenatal care, where the diagnosis is performed, the treatment offered and the reception of this pregnant woman performed.